Degeneration and damage mechanism of Pseudomorphic Glass under 170 keV proton irradiation. (December 2021) - Zhao, Huiyang; Wang, Hao; Guo, Hongliang; Wu, You; Sun, Chengyue; Yu, Hui; Cui, Xinyu; Wu, Yiyong; Guo, Bin
Abstract: As the covering layer of flexible solar cells, Pseudomorphic Glass (PMG) needs brilliant optical, mechanical and radiation protection properties to ensure the long-term stable operation of cells. In this paper, the evolution law and mechanism analysis of PMG optical and mechanical properties under 170 keV proton irradiation were studied systematically. The surface morphology and the occurrence of cracks before and after irradiation were observed by OLYMPUS optical microscope and SEM. The degradation characteristics of PMG optical performance were researched by comparing the changes of RTV sheet and PMG transmittance. FT-IR and XPS were used to study the vicissitudes of surface composition and chemical bonds, and based on this, the degradation and crosslinking mechanism of silicon rubber molecular chains after proton irradiation was given. In addition, the stress-strain test was selected to characterize the mechanical properties of PMG. Highlights: ∙ The optical and mechanical properties of PMG before and after proton irradiation were studied systematically. ∙Cracks were formed on the surface of PMG after irradiation. When the fluence reached 1 × 10 16 cm −2, a convex structure appeared and the cracks connected into a network. ∙The transmittance absorption peak intensity of the irradiated PMG showed about 10% lower than that of the RTV counter-part, implying better anti-darkening behavior for the composite PMG. ∙The Eb decreased while TSb increased with the increase of proton irradiation fluence, which is due to the enhancement of bonding force between the glass beads and adhesive interface caused by irradiation.